A Proto-brown Dwarf Candidate in Rho Ophiuchus - Ngoc, Phan Bao (Communications in Physics, 2022)
Brown dwarfs with masses below 0.075 solar masses are thought to form like low-mass stars (e.g., the Sun).However, it is still unclear how the physical formation processes occur in brown dwarfs at the ealiest stages (i.e., proto-brown dwarfs) of their formation. Up to date, only a few proto-brown dwarfs have been detected. The detection of proto-brown dwarfs offers us excellent benchmarks to study the formation process of brown dwarfs, and thus understand their formation mechanism.In this paper, we present our identification of a proto-brown dwarf candidate in the star-forming region\(ρ\) Ophiuchus. The candidate shows a small-scale bipolar molecular outflow that is similar to the outflows observed inother young brown dwarfs. The detection of this candidate provides us with additional important implications for the formation mechanism of brown dwarfs.